STRATEGI PENANGANAN PERUDUNGAN MELALUI PENGINTEGRASIAN KETERAMPILAN SOSIAL SALING MENGHARGAI - susiani, ketut; Suranata, Kadek; Ardana, I Wayan; Sari, Ni Made Dainivitri Sinta (Jurnal Penjaminan Mutu, 2025)
This study investigates verbal bullying in elementary schools, which commonly occurs in the form of mockery, name-calling, and verbal abuse. This study aims to identify the causes and impacts of verbal bullying and offer a strategy for its prevention through the integration of mutual respect social skills in the learning process. Using a qualitative descriptive approach with interviews and observations at SDN 3 Kebon Padangan, the findings indicate that verbal bullying is mainly caused by students’ lack of empathy and social awareness. The school’s current efforts, such as involving teachers and parents in problem-solving, are still insufficient. Therefore, this study proposes the integration of mutual respect skills in classroom activities as a strategic solution to foster empathy, reduce bullying, and create a more harmonious school environment.